2010
DOI: 10.1128/mcb.00852-09
|View full text |Cite
|
Sign up to set email alerts
|

Control of Adipogenesis by the SUMO-Specific Protease SENP2

Abstract: Here, we demonstrate that SENP2, a desumoylating enzyme, plays a critical role in the control of adipogenesis. SENP2 expression was markedly increased upon the induction of adipocyte differentiation, and this increase was dependent on protein kinase A activation. Remarkably, knockdown of SENP2 led to a dramatic attenuation of adipogenesis with a marked decrease in PPAR␥ and C/EBP␣ mRNA levels. Knockdown of SENP2 also caused a marked reduction in the level of C/EBP␤ protein but not in that of C/EBP␤ mRNA. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 47 publications
1
67
0
1
Order By: Relevance
“…The effect of UBC9 knockdown on the expression levels of adipogenic transcription factors is of interest, in view of the reported ability of UBC9 to modulate PPAR␥ transcriptional activity through SUMOylation of specific amino acid residues in this transcription factor (31)(32)(33). Other adipogenic transcription factors, such as C/EBP␣ and C/EBP␤, are also SUMOylated (34,35), and it has recently been suggested that interfering with the de-SUMOylation step via knockdown of a specific SUMO protease, such as SENP2 (SUMO1/sentrin/SMT3 specific peptidase-2), affects C/EBP␤ stability and the extent of adipogenesis (36). However, in this study, overexpression of the catalytically inactive mutant of UBC9, in which the cysteine residue (Cys93) required for the SUMO-conjugating activity of the enzyme was replaced by alanine, resulted in indistinguishable effects on C/EBP␦, C/EBP␣, and PPAR␥ mRNA expression as well as on overall adipogenesis, compared with both UBC9-overexpressing and mock-infected cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of UBC9 knockdown on the expression levels of adipogenic transcription factors is of interest, in view of the reported ability of UBC9 to modulate PPAR␥ transcriptional activity through SUMOylation of specific amino acid residues in this transcription factor (31)(32)(33). Other adipogenic transcription factors, such as C/EBP␣ and C/EBP␤, are also SUMOylated (34,35), and it has recently been suggested that interfering with the de-SUMOylation step via knockdown of a specific SUMO protease, such as SENP2 (SUMO1/sentrin/SMT3 specific peptidase-2), affects C/EBP␤ stability and the extent of adipogenesis (36). However, in this study, overexpression of the catalytically inactive mutant of UBC9, in which the cysteine residue (Cys93) required for the SUMO-conjugating activity of the enzyme was replaced by alanine, resulted in indistinguishable effects on C/EBP␦, C/EBP␣, and PPAR␥ mRNA expression as well as on overall adipogenesis, compared with both UBC9-overexpressing and mock-infected cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, PIAS1 is a negative regulator in adipogenesis by promoting the SUMOlation and degradation of C/EBP␤. Conversely, the SUMO-specific protease Sentrin/SUMO-specific protease 2 (SENP2) plays a critical role in promoting adipogenesis by de-SUMOlation and stabilization of C/EBP␤ (70).…”
Section: Post-translational Modifications (Ptms) Of C/ebp␤ During Adimentioning
confidence: 99%
“…SENP1 de-SUMOylates Sharp-1, not C/EBP␤, a target of SENP2 in adipogenesis. Interestingly, Chung et al (24) didn't detect any change of SENP1 expression in 3T3-L1 induced by DMI. However, in our study, we clearly demonstrated the increase of SENP1 in MEF cells when induced by DMIR.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al (23) found that PIAS1 promotes C/EBP␤ SUMOylation and inhibits adipogenesis. Chung et al (24) found that a de-SUMOylation protease, SENP2, can directly modulate C/EBP␤ SUMOylation and its stability and, consequently, is essential for adipogenesis. Here we provide more evidence for SUMOylation in the regulation of adipogenesis by showing that SENP1, another member of SENP family, is also essential for adipogenesis.…”
Section: Discussionmentioning
confidence: 99%